2018
DOI: 10.1101/499897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective neuronal vulnerability in Alzheimer’s disease: a network-based analysis

Abstract: A major obstacle to treating Alzheimer's disease (AD) is our lack of understanding of the molecular mechanisms underlying selective neuronal vulnerability, which is a key characteristic of the disease. Here we present a framework to integrate highquality neuron-type specific molecular profiles across the lifetime of the healthy mouse, which we generated using bacTRAP, with postmortem human functional genomics and quantitative genetics data. We demonstrate human-mouse conservation of cellular taxonomy at the mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 92 publications
2
23
0
Order By: Relevance
“…Patterns of alteration in glutamatergic neurons reveal an anatomical pattern of neuronal impact across human hippocampal substructures, with CA1 pyramidal neurons most affected, followed by pyramidal neurons of entorhinal deep and mid layers, and ending up with CA3 neurons and DG granule cells which show the least effect. These observations are consistent with the selective vulnerability of CA1 and EC pyramidal cells 11,21,39 , and suggest that observed transcriptomic responses may reflect molecular processes relevant for neuronal dysfunction. Potentially among the latter, we found that CA1 neurons show simultaneous downregulation of homeostatic neuronal functions and upregulation of processes suggestive of neuronal stress, including metabolic alterations, cytoskeletal transport dysfunction, inflammatory responses, and genes involved in neurodegeneration.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Patterns of alteration in glutamatergic neurons reveal an anatomical pattern of neuronal impact across human hippocampal substructures, with CA1 pyramidal neurons most affected, followed by pyramidal neurons of entorhinal deep and mid layers, and ending up with CA3 neurons and DG granule cells which show the least effect. These observations are consistent with the selective vulnerability of CA1 and EC pyramidal cells 11,21,39 , and suggest that observed transcriptomic responses may reflect molecular processes relevant for neuronal dysfunction. Potentially among the latter, we found that CA1 neurons show simultaneous downregulation of homeostatic neuronal functions and upregulation of processes suggestive of neuronal stress, including metabolic alterations, cytoskeletal transport dysfunction, inflammatory responses, and genes involved in neurodegeneration.…”
Section: Discussionsupporting
confidence: 83%
“…We next sought to pinpoint specific anatomical structures and neuronal subtypes where AD-associated changes preferentially occur, by quantifying the association between gene expression levels and neurofibrillary tangle pathology (NFT) burden for each neuronal subtype separately ( Supplementary Table S9 ). Given the intracellular and selective character of NFT pathology 22 , we used a targeted approach to uncover molecular processes potentially mediating neuronal dysfunction, specifically focusing on anatomical structures and neuronal populations that are robustly annotated, directly targeted during tissue recollection, and expected to include neurons that are vulnerable to neurodegeneration 21,39 . For glutamatergic neurons, we focused on CA1, CA3, and DG subtypes from the hippocampus ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-type specific profiling technologies have made it possible to characterize their gene expression profiles, but how genes operate in the specific context of these cells and how they are related to disease cannot be readily parsed out by mere profiling. We recently used high quality molecular signatures of ECII neurons along with a large compendium of genomics data to build maps of functional gene interactions within the context of ECII neurons (Roussarie et al, 2020). Contrasting ECII neurons with neurons more resistant to AD, we found that pathways related to microtubule remodeling were particularly salient in ECII neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting ECII neurons with neurons more resistant to AD, we found that pathways related to microtubule remodeling were particularly salient in ECII neurons. To investigate AD processes in the specific context of ECII neurons we used our NetWAS 2.0 (Network-Wide Association Study 2.0) algorithm, which leveraged our ECII functional map along with genome wide association study data for NFT formation (Beecham et al, 2014; Roussarie et al, 2020). NetWAS 2.0 re-prioritized genes based on their association with tau pathology within vulnerable neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation